NILAI THEOLOGIS DALAM SERAT WEDHATAMA - -, Purwadi (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2007)
Serat Wedhatama is a Javanese literary work by Sri Mangkunegara IV. Itcontains considerable piwulang luhur (or valuable teachings) in the ethics of life insocial interaction. This article concerns a research aiming at describing thetheological values in Serat Wedhatama which are often referred to as SembahRaga, Sembah Cipta, Sembah Jiwa, and Sembah Rasa. They are said to coincidewith what are usually referred to in Moslem sufism as syariat, tarikat, hakikat, andmakrifat as well as with what are always referred to in Hinduism as artha, kama,dharma, and muksa. In that work of his, Sri Mangkunegara IV is able to make asuccessful discourse of harmony among traditional Javanese principles, Islamicprinciples, and Hindu principles. Serat Wedhatama could thus become importantreading for Javanese people.Keywords : theology, Serat Wedhatama, ethics of life